Methylglyoxal, Glycated Albumin, PAF, and TNF-α: Possible Inflammatory and Metabolic Biomarkers for Management of Gestational Diabetes - Gabriele Piuri (Nutrients, 2020)
Background: In gestational diabetes mellitus (GDM), pancreatic β-cell breakdown can result from a proinflammatory imbalance created by a sustained level of cytokines. In this study, we investigated the role of specific cytokines, such as B-cell activating factor (BAFF), tumor necrosis factor α (TNF-α), and platelet-activating factor (PAF), together with methylglyoxal (MGO) and glycated albumin (GA) in pregnant women affected by GDM. Methods: We enrolled 30 women whose inflammation and metabolic markers were measured at recruitment and after 12 weeks of strict dietetic therapy. We compared these data to the data obtained from 53 randomly selected healthy nonpregnant subjects without diabetes, hyperglycemia, or any condition that can affect glycemic metabolism. Results: In pregnant women affected by GDM, PAF levels increased from 26.3 (17.4−47.5) ng/mL to 40.1 (30.5−80.5) ng/mL (p < 0.001). Their TNF-α levels increased from 3.0 (2.8−3.5) pg/mL to 3.4 (3.1−5.8) pg/mL (p < 0.001). The levels of methylglyoxal were significantly higher in the women with GDM (p < 0.001), both at diagnosis and after 12 weeks (0.64 (0.46−0.90) μg/mL; 0.71 (0.47−0.93) μg/mL, respectively) compared to general population (0.25 (0.19−0.28) μg/mL). Levels of glycated albumin were significantly higher in women with GDM (p < 0.001) only after 12 weeks from diagnosis (1.51 (0.88−2.03) nmol/mL) compared to general population (0.95 (0.63−1.4) nmol/mL). Conclusion: These findings support the involvement of new inflammatory and metabolic biomarkers in the mechanisms related to GDM complications and prompt deeper exploration into the vicious cycle connecting inflammation, oxidative stress, and metabolic results.